The Rhythm of the Gods’ Voice. The Suggestion of Divine Presence through Prosody - Blankenborg, Ronald (ARYS. Antigüedad: Religiones y Sociedades, 2020)
In this article, I draw attention to the gods’ pickiness in the audible flow of their utterances, a prosodic characteristic of speech that evokes the presence of the divine. Hexametric poetry itself is the language of permanency, as evidenced by wisdom literature, funereal and dedicatory inscriptions: epic poetry is the embedded direct speech of a goddess. Outside hexametric poetry, the gods’ special speech is primarily expressed through prosodic means, notably through a shift in rhythmic profile. Such a shift deliberately captures, or recalls, the well-known rhythmic profiles, phrases, and clausulae from epic and wisdom literature. Embedded in other prosodic profiles, these audibly alienating and isolated utterances both bewilder through their unexpected appearance, and reassure because of their familiarity for the listening audience. Resembling and evoking the language of permanency for embedded divine speech, quotations in hexameter lend a sense of ritual to their performance in other rhythmic environments. A performer temporarily impersonates a speaking divinity, as the audience experiences the revelation’s premiere staging.
Keywords: re-enactment; rhythm; ritual; situational flickering; stylized speech